Virucity. Rethinking the urban system - Fistola, Romano; Borri, Dino (TeMA - Journal of Land Use, Mobility and Environment, 2020)
The paper focuses attention on three fundamental points. The first one concerns an analysis of the urban condition perceived and detected directly by the observation of the city suddenly deprived of the fruition component and characterized by the functional reset of urban activities with the exception of health functions. The second element is attributable to a systemic interpretation of the phenomenon through the analysis of the effects on urban subsystems produced by the pandemic, recalling the holistic approach to the study of urban phenomena. The third element concerns the envisaging of possible post-virus urban scenarios for which a significant bifurcation is foreseen: on the one hand, if the virus produced a rethinking of life models and the need for new ways of acting and interacting in the city we could imagine an urban future characterized by a general rebalancing of anthropic contexts; on the other hand, if the desire to return to entropic and energy-consuming models will prevail, we will continue to witness the slow degradation of human and natural habitats that will lead to the “right” extinction of human beings. These alternatives underlie a series of dilemmas that the paper emphasizes as structuring elements of possible future urban scenarios, highlighting the fundamental role of urban scientists and planners.